Why are children different in their moderate‐to‐vigorous physical activity levels? A multilevel analysis - Sara Pereira; Ana Reyes; Marcos A. Moura‐Dos‐Santos; Carla Santos; Thayse N. Gomes; Go Tani; Olga Vasconcelos; Tiago V. Barreira; Peter T. Katzmarzyk; José Maia (Brazilian Society of Pediatrics, 2020)
Objective: Children's differences in moderate‐to‐vigorous physical activity levels are not at random. This study investigates the relevance of individual‐ and school‐level characteristics in explaining these differences. Methods: In total, 307 children (154 girls) aged 5-10 years, from 19 Portuguese schools, were sampled. Height and weight were measured, and body mass index was calculated. Time spent in moderate‐to‐vigorous physical activity was measured by accelerometry. Gross motor coordination was assessed with the KörperkoordinationsTest für Kinder battery and socio‐economic status was obtained via the school social support system. School characteristics were obtained with an objective school audit. A multilevel analysis was used as implemented in Stata 15. Results: Schools explained 18.2% of the total variance in moderate‐to‐vigorous physical activity, with the remainder being ascribed to children's distinct characteristics. Boys were more active (β = 29.59 ± 11.52, p < 0.05), and having higher gross motor coordination levels (β = 0.11 ± 0.04, p < 0.05) was positively associated with daily moderate‐to‐vigorous physical activity, whereas being older (β = −5.00 ± 1.57, p < 0.05) and having higher socio‐economic status (β = −7.89 ± 3.12, p < 0.05) were negatively related with moderate‐to‐vigorous physical activity. From the school‐level correlates, only playground dimension was significantly associated with moderate‐to‐vigorous physical activity levels. Children from schools with medium (40 m2 to 69 m2) and large playground dimensions (≥70 m2) were less active than children with smaller playground dimensions (10 m2 to 39 m2). Conclusions: Variation in school children's moderate‐to‐vigorous physical activity is mostly explained by their individual characteristics; school characteristics also play a role but to a smaller degree. Future intervention programs to change this behavior should be more personalized, emphasizing mostly individual‐level characteristics. Resumo: Objetivo: As diferenças entre crianças na atividade física moderada a vigorosa não são aleatórias. Este estudo investiga a relevância das características em níveis individuais e escolares para explicar essas diferenças. Métodos: Foram amostradas 307 crianças (154 meninas) entre 5 e 10 anos, de 19 escolas portuguesas. A estatura e o peso foram medidos e o índice de massa corporal foi calculado. O tempo gasto em atividade física moderada a vigorosa foi medido por acelerometria. A coordenação motora grossa foi avaliada com a bateria do Körperkoordinationstest für Kinder e o status socioeconômico foi obtido através do sistema de apoio social da escola. As características da escola foram obtidas através de uma auditoria escolar objetiva. Uma análise multinível foi utilizada como implantada no Stata 15. Resultados: As escolas explicaram 18,2% da variância total da atividade física moderada a vigorosa, com o restante atribuído às diferentes características das crianças. Os meninos foram mais ativos (β = 29,59 ± 11,52, p < 0,05) e o fato de ter níveis mais altos de coordenação motora grossa (β = 0,11 ± 0,04, p < 0,05) foi positivamente associado com a atividade física moderada a vigorosa diária. Os mais velhos (β = ‐5,00 ± 1,57, p < 0,05) e com maior status socioeconômico (β = ‐7,89 ± 3,12, p < 0,05) foram negativamente relacionados com a atividade física moderada a vigorosa. Com base nos correlatos a nível escolar, apenas a dimensão da área recreativa foi significativamente associada aos níveis de atividade física moderada a vigorosa. As crianças das escolas com área recreativa média (40 m2 a 69 m2) e grande (≥ 70 m2) foram menos ativas do que as crianças com áreas recreativas com menores dimensões (10 m2 a 39 m2). Conclusões: A variação na atividade física moderada a vigorosa de escolares é explicada principalmente por suas características individuais; as características da escola também desempenham um papel, mas em menor grau. Futuros programas de intervenção para mudar esse comportamento devem ser mais personalizados, enfatizar principalmente as características em nível individual. Keywords: Child, School environment, Physical activity, Multilevel modeling, Palavras‐chave: Criança, Ambiente escolar, Atividade física, Modelagem multinível